The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.15226/jnhfs.2014.00130
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity among Adolescents in Senior Secondary Schools in Oyo State, Nigeria

Abstract: Lagos, Nigeria Ben-Bassey et al. [7] reported overall prevalence rates of overweight and obesity in the urban and rural areas to be 3.7% and 0.4%, and 3.0% and 0.0%, respectively. Furthermore, the prevalence rates of obesity and being overweight in a study carried out in Cross River, Nigeria were 1.7% and 6.8%, respectively [8]. Considering the importance of obesity complications for the health state of society and its increasing rate, careful evaluation, monitoring and follow up of obesity in children and ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(9 reference statements)
1
1
0
Order By: Relevance
“…The difference in the overweight and obesity status could be linked to hypokinetic lifestyle of the male students attending the private schools such as increase in number hours for playing computer games, watching television, reduced physical movement to schools and probably disordered eating pattern (Ogunjimi, 2009;Wang & Lobstein 2012;Ekpenyong & Akpan, 2012). This finding was also corroborated by Akinlade, Afolabi, Oguntona and Agbonlahor (2012) who also reported a higher prevalence among the students in the private schools than in the public. Several studies that had been conducted revealed that pupils in the private high schools tend to be overweight than their public counterparts and this study is no deviation from the established claims.…”
Section: Discussionsupporting
confidence: 73%
“…The difference in the overweight and obesity status could be linked to hypokinetic lifestyle of the male students attending the private schools such as increase in number hours for playing computer games, watching television, reduced physical movement to schools and probably disordered eating pattern (Ogunjimi, 2009;Wang & Lobstein 2012;Ekpenyong & Akpan, 2012). This finding was also corroborated by Akinlade, Afolabi, Oguntona and Agbonlahor (2012) who also reported a higher prevalence among the students in the private schools than in the public. Several studies that had been conducted revealed that pupils in the private high schools tend to be overweight than their public counterparts and this study is no deviation from the established claims.…”
Section: Discussionsupporting
confidence: 73%
“…The few studies on adolescent obesity in Nigeria focused mainly on the prevalence, with little or nothing on the determinants. [38][39][40][41] More studies are required to elaborate on the in uence of different factors on adolescent obesity as this will inform effective prevention and intervention programmes. This study therefore aimed to determine the prevalence of obesity and its association with socio-demographic pro le, lifestyle factors, dietary patterns and physical activity patterns among in-school adolescents in Southwest, Nigeria.…”
Section: Introductionmentioning
confidence: 99%